A Novel Gene, OZONE-RESPONSIVE APOPLASTIC PROTEIN1, Enhances Cell Death in Ozone Stress in Rice. Issue 1 (28th July 2015) - Ueda, Yoshiaki; Siddique, Shahid; Frei, Michael
Abstract : Polymorphisms in the promoter sequence are a novel, ozon-responsive protein suggested to affect ozone tolerance in contrasting cultivars. Abstract: A novel protein, OZONE-RESPONSIVE APOPLASTIC PROTEIN1 (OsORAP1), was characterized, which was previously suggested as a candidate gene underlying OzT9, a quantitative trait locus for ozone stress tolerance in rice ( Oryza sativa ). The sequence of OsORAP1 was similar to that of ASCORBATE OXIDASE (AO) proteins. It was localized in the apoplast, as shown by transient expression of an OsORAP1/green fluorescent protein fusion construct in Nicotiana benthamiana leaf epidermal and mesophyll cells, but did not possess AO activity, as shown by heterologous expression of OsORAP1 in Arabidopsis ( Arabidopsis thaliana ) mutants with reduced background AO activity. A knockout rice line of OsORAP1 showed enhanced tolerance to ozone stress (120 nL L −1 average daytime concentration, 20 d), as demonstrated by less formation of leaf visible symptoms (i.e. cell death), less lipid peroxidation, and lower NADPH oxidase activity, indicating reduced active production of reactive oxygen species. In contrast, the effect of ozone on chlorophyll content was not significantly different among the lines. These observations suggested that OsORAP1 specifically induced cell death in ozone stress. Significantly enhanced expression of jasmonic acid-responsive genes in the knockout line implied the involvement of the jasmonic acid pathway in symptom mitigation. Sequence analysis revealed extensive polymorphisms in the promoter region of OsORAP1 between the ozone-susceptible cv Nipponbare and the ozone-tolerant cv Kasalath, the OzT9 donor variety, which could be responsible for the differential regulation of OsORAP1 reported earlier. These pieces of evidence suggested that OsORAP1 enhanced cell death in ozone stress, and its expression levels could explain the effect of a previously reported quantitative trait locus.